2015
DOI: 10.5194/angeo-33-1173-2015
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of concurrent Pc5 and chorus waves on relativistic electron dynamics

Abstract: Abstract. We present electron phase space density (PSD) calculations as well as concurrent Pc5 and chorus wave activity observations during two intense geomagnetic storms caused by interplanetary coronal mass ejections (ICMEs) resulting in contradicting net effect. We show that, during the 17 March 2013 storm, the coincident observation of chorus and relativistic electron enhancements suggests that the prolonged chorus wave activity seems to be responsible for the enhancement of the electron population in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
5
14
0
Order By: Relevance
“…Note that the maximum chorus amplitude also moved from L ≈4.7 to L * ≈6.3 during 21–25 April. This result is consistent with the findings of Katsavrias, Daglis, Li, et al () who showed that, during the March 2013 intense storm and concerning the >300‐MeV/G electrons, the chorus‐driven acceleration exceeded the Pc5‐driven losses. After 24 April, PSD gradients were continuously positive with gradual decrease.…”
Section: Resultssupporting
confidence: 92%
“…Note that the maximum chorus amplitude also moved from L ≈4.7 to L * ≈6.3 during 21–25 April. This result is consistent with the findings of Katsavrias, Daglis, Li, et al () who showed that, during the March 2013 intense storm and concerning the >300‐MeV/G electrons, the chorus‐driven acceleration exceeded the Pc5‐driven losses. After 24 April, PSD gradients were continuously positive with gradual decrease.…”
Section: Resultssupporting
confidence: 92%
“…We note similar results by Katsavrias et al (2015), who examined only a single EA and IA event, and that of Ma et al (2018) but without a discussion on morphological similarities. We note similar results by Katsavrias et al (2015), who examined only a single EA and IA event, and that of Ma et al (2018) but without a discussion on morphological similarities.…”
Section: Discussionsupporting
confidence: 81%
“…of Figure 16 we observe that, during storm time, ULF power in the range of Pc5 (2-7 mHz) across the magnetosphere increases by two to three orders of magnitude, leading to a corresponding enhancement of the diffusion coefficients of >300 keV electrons, and hence to enhanced outward diffusion (Mann et al 2012;Katsavrias et al 2015). Since ULF wave power is correlated with the solar-wind dynamic pressure (e.g., Kepko & Spence 2003;Liu et al 2010), we can expect that the magnetospheric compression caused by the arrival of the IP shock at 1 AU (see Section 6.1) could have led to the observed enhancement of ULF waves, which in turn contributed to the observed radial losses of relativistic particles.…”
Section: Radiation Belt Dynamicsmentioning
confidence: 89%